A High-Fat Diet Increases Influenza A Virus-Associated Cardiovascular Damage. (4th April 2020) - Siegers, Jurre Y; Novakovic, Boris; Hulme, Katina D; Marshall, Rebecca J; Bloxham, Conor J; Thomas, Walter G; Reichelt, Mellissa E; Leijten, Lonneke; van Run, Peter; Knox, Karen; Sokolowski, Kamil A; Tse, Brian W C; et al.
Abstract: Background: Influenza A virus (IAV) causes a wide range of extrarespiratory complications. However, the role of host factors in these complications of influenza virus infection remains to be defined. Methods: Here, we sought to use transcriptional profiling, virology, histology, and echocardiograms to investigate the role of a high-fat diet in IAV-associated cardiac damage. Results: Transcriptional profiling showed that, compared to their low-fat counterparts (LF mice), mice fed a high-fat diet (HF mice) had impairments in inflammatory signaling in the lung and heart after IAV infection. This was associated with increased viral titers in the heart, increased left ventricular mass, and thickening of the left ventricular wall in IAV-infected HF mice compared to both IAV-infected LF mice and uninfected HF mice. Retrospective analysis of clinical data revealed that cardiac complications were more common in patients with excess weight, an association which was significant in 2 out of 4 studies. Conclusions: Together, these data provide the first evidence that a high-fat diet may be a risk factor for the development of IAV-associated cardiovascular damage and emphasizes the need for further clinical research in this area. Abstract : Experimental and preliminary epidemiological evidence supports a high-fat diet as potential risk factor for the development of cardiac complications following influenza virus infection.